Engine Performances of Lean Iso-Octane Mixtures in a Glow Plug Heated Sub-Chamber SI Engine - Willyanto Anggono; Soen Peter Stanley; Ferdinand Ronaldo; Gabriel J. Gotama; Bin Guo; Emir Yilmaz; Mitsuhisa Ichiyanagi; Takashi Suzuki (Automotive Experiences, 2022)
Due to the difficulty to directly study ammonia, the present work investigated the engine performance of lean iso-octane/air mixture to approximate ammonia combustion behaviour. The study was conducted using a single cylinder modified diesel engine that features a spark plug and glow plug in the sub-chamber. The investigations varied the engine speeds (1000 and 1500 RPM), glow plug voltages (6 and 10 volts), excess air ratios (1.4 to 1.8), and ignition timings (-2 to -5 Â°BTDC). The results suggested improved engine performances with a lower excess ratio and higher glow plug voltage due to more complete and stable combustion. By increasing the engine speed, the lean burn limit was extended and improved the engine performances. Because of the sub-chamber feature, delaying the ignition timing improved the engine performances. A larger excess air ratio was found to increase the sensitivity of the engine performances with the ignition timing. The brake mean effective pressure for all conditions has a coefficient of variation of less than 7%, indicating stable combustion. The results suggested that the current setup can be used to investigate ammonia blended fuel and direct ammonia combustion in future works.